The value of water for irrigated paddy and hydropower generation in the Great Ruaha, Tanzania - Kadigi, R. M. J.; Mdoe, N.S.Y.; Lankford, B.A.; Morardet, Sylvie (2005)
The need to achieve efficient, equitable and sustainable use of water resources to meet water demands of different sectors is pressing, particularly in areas where water resources are dwindling. Along with this is the quest for a good understanding of the value of water in its different uses. Using the Change in Net Income method, this paper presents an assessment of the value of water in irrigated paddy and hydroelectric power (HEP) generation in the Great Ruaha (GR) Catchment in Tanzania. The average values of water for irrigated paddy were estimated at $ 0.01 and 0.04 per m3 for abstracted and consumed water respectively. For HEP, the values were relatively higher ($ 0.06-0.21 per m3 for gross and consumed water respectively). Yet irrigated paddy also contributes much: it supports the livelihoods of about 30,000 agrarian families in Usangu with average annual gross income of about US $ 911.90 per annum per family and the GR paddy contributes about 14-24% to national paddy production. Understanding these benefits is key to fostering informed debate on water management and allocation, identifying the base for making ?agreeable? trade-offs, the potential for improvement, and creating linkages with water allocation options.